(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background individuals with chronic obstructive pulmonary diseases (COPD) showed balance control deficits with a suggested relevance to increased fall risk. So, studies suggest balance training to be a complementary component of COPD rehabilitation program. Aim this study aimed to examine the effects of balance training using Biodex balance system on balance control in COPD patients. Methods thirty patients with COPD from the October 6 University Hospital outpatient clinic and University employees were recruited. Patients ranged between 50 to 60 years in age. After their recruitment, patients had been assigned at random into Biodex training group (BTG) and control group (CG). Patients in BTG (n= 15) participated in a 8 weeks program implementing balance training using Biodex balance system, conventional balance training, and breathing exercise for 3 times/week. Patients in CG (n=15) applied conventional balance training and breathing exercise only. Postural stability test (PST) and fall risk test (FRT) using Biodex balance system, in addition to Berg Balance score (BBS) were used for pre- and post- experimental testing. Result Outcomes of comparisons demonstrated statistically significant improvements in all measured variables within both BTG and CG (P< 0.05). Meanwhile, between groups comparisons showed significantly higher improvements has been reported in favour of BTG in all outcomes. Conclusion Balance training using Biodex balance system is recommended for balance training in patients with COPD to correct deficits in balance control and reduce fall risk.